Enhancing the heavy load performance of a gasoline engine converted for LPG use by modifying the ignition timings - Erkus, Baris; Karamangil, M. Ihsan; Sürmen, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
This paper presents the results of the experiments conducted on a spark-ignition (SI) engine fuelled with liquefied petroleum gas (LPG) by varying the ignition timing at the excess air coefficients of 1.0 and 1.3. Experiments were carried out at wide open throttle (WOT) position and at engine speed of 4300 rpm aiming to determine the lean operation performance of an engine when fuelled with LPG at full load. Performance parameters, namely brake power, brake-specific fuel consumption (BSFC), brake thermal efficiency and exhaust emissions such as unburned hydrocarbons (HC), carbon monoxide (CO) and nitrogen oxides (NOx), were studied. It was shown that advancing the ignition timing improved the performance of LPG-fuelled SI engine for excess air coefficients higher than 0.8. The highest brake power and the lowest BSFC were obtained with modified ignition timing at an excess air coefficient of 1.0. The lowest exhaust emissions were obtained with an excess air coefficient of 1.3. In general, advancing the ignition timings caused increase in HC and NO emissions, while the effect of ignition timing on CO emissions was negligible.
Keywords: SI engine; LPGECU tuning; Ignition timing; Excess air coefficient